LITERARY TRANSLATION AND ITS FEATURES IN UZBEK PROSE RELATING TO THE TWENTIETH CENTURY (Proceedings of International Educators Conference, 2022)
Translation is a crucial matter to us at Responsive Translation. We also enjoy fantastic quotes because they provide us with quick bursts of inspiration that can make us laugh, ponder, or sometimes even do both. Here are some of our preferred translation quotes